2017
DOI: 10.1111/jth.13847
|View full text |Cite
|
Sign up to set email alerts
|

Phase IIa study of dabigatran etexilate in children with venous thrombosis: pharmacokinetics, safety, and tolerability

Abstract: Tartakovsky I, Mitchell LG. Phase IIa study of dabigatran etexilate in children with venous thrombosis: pharmacokinetics, safety, and tolerability.J Thromb Haemost 2017; 15: 2147-57. EssentialsDabigatran etexilate may provide a new treatment option for pediatric venous thromboembolism. Children aged 1 to < 12 years were given dabigatran etexilate in an open-label, single-arm study. The pharmacokinetic-pharmacodynamic relationship was similar to that seen in adult patients. There were no serious adverse events,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…However, phase 2 pediatric trials of rivaroxaban and dabigatran were recently published and phase 3 trials (clinicaltrial.gov identifiers: NCT02234843 and NCT01895777, respectively) are nearing completion. 140,141 Thus, these agents may soon be available for pediatric use. Anticoagulant dosing in children is complex because of age-related hemostasis system maturation as well as pharmacokinetic differences compared to adults.…”
Section: Childhood Kidney Diseasementioning
confidence: 99%
“…However, phase 2 pediatric trials of rivaroxaban and dabigatran were recently published and phase 3 trials (clinicaltrial.gov identifiers: NCT02234843 and NCT01895777, respectively) are nearing completion. 140,141 Thus, these agents may soon be available for pediatric use. Anticoagulant dosing in children is complex because of age-related hemostasis system maturation as well as pharmacokinetic differences compared to adults.…”
Section: Childhood Kidney Diseasementioning
confidence: 99%
“…The three paediatric trials were: study 1160.88 (NCT00844415; patients aged 12 to < 18 years), study 1160.89 (NCT01083732; patients aged 1 to < 12 years) and study 1160.105 (NCT02223260; patients aged < 1 year), details of which have previously been reported. 20 21 22 Study 1160.88 was a phase IIa, open-label, multi-centre, single-arm trial to evaluate the safety and tolerability and assess preliminary pharmacokinetic (PK) and PD parameters of dabigatran in adolescent patients, aged between 12 and < 18 years. After successfully completing treatment with LMWH or oral anticoagulation for primary VTE, patients received weight-adjusted doses of DE administered as capsules twice daily for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…However, this was replaced with a single age- and weight-adjusted dose during the course of the study. 21 Study 1160.105 was a phase IIa, open-label, multi-centre, single-arm trial to assess the PK/PD relationship, safety and tolerability of DE in infants aged < 1 year, who had completed standard anticoagulant treatment for VTE. Infants received a single age- and weight-adjusted dose of DE, administered as an oral liquid formulation.…”
Section: Methodsmentioning
confidence: 99%
“…There have been no completed randomized controls trials as yet using DOACS to treat VTE or for thromboprophylaxis although several phase III trials are underway for rivaroxaban (EINSTEIN Junior) dabigatran and apixaban . A phase II study of dabigatran in 18 children aged 2‐12 years old has shown that the pharmacokinetics are like that of adults with no significant bleeding or recurrent VTE . Similar trials of rivaroxaban and apixaban have yet to report.…”
Section: Drug Characteristicsmentioning
confidence: 99%
“…9 A phase II study of dabigatran in 18 children aged 2-12 years old has shown that the pharmacokinetics are like that of adults with no significant bleeding or recurrent VTE. 16 Similar trials of rivaroxaban and apixaban have yet to report. There are pharmacokinetic studies for rivaroxaban and apixaban that have been described in the neonatal and pediatric populations which have been compared to adults showing similar anti-Xa effects in all age groups.…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 99%